Immunization with a Plasmodium falciparum merozoite surface antigen induces a partial immunity in monkeys. - Perrin, L H (1985)
Saimiri monkeys immunized with a Plasmodium falciparum merozoite polypeptide of 41 kD mol wt are resistant to a blood challenge infection that induces a fulminant infection in control monkeys. The sera of the immunized monkeys reacted, as shown by the indirect immunofluorescence technique, with the apical part of the merozoites from five isolates or clones of P. falciparum. Whether the immunogen was dissolved in nonionic detergent (NP-40) or in sodium dodecyl sulfate (SDS) had a marked influence on the level of protection in immunized monkeys. Thus, monkeys immunized with the antigen solubilized in a nonionic detergent developed much lower parasitemia than monkeys immunized with denatured antigen (antigen eluted from SDS polyacrylamide gel electrophoresis).